The Impact of the Qur’anic Text on Critical Judgments in the Works of Diya al-Din Ibn al-Athir - raache, amina (El Omda in Linguistics and Discourse Analysis, 2018)
<section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-(--header-height)" dir="auto" data-turn-id="c2ce28c7-ca36-4518-92aa-2e4890444ea2" data-testid="conversation-turn-3" data-scroll-anchor="false" data-turn="user"> <section class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:a86af89b-1479-4b9c-b50c-e9d5466cf18b-1" data-testid="conversation-turn-4" data-scroll-anchor="true" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="80d31d27-4ebf-4495-9736-9c0a6e7904e8" data-message-model-slug="gpt-5-3" data-turn-start-message="true"> This study aims to reveal the dominance of the Qur’anic text, as the highest artistic and literary model, over Ibn al-Athir’s critical standards, based on the concept of absolute beauty embodied in this text. Ibn al-Athir aspired to align his critical criteria with the language of the Holy Qur’an and to harmonize them with its modes of expression. This ambition is clearly reflected in the standards he adopted, leading him to reject many of the established assumptions rooted in classical criticism. He did not accept the opinions of others without first subjecting them to this inimitable rhetorical text and evaluating them according to its measure.